The Urbanization of Green Internationalism - Dierwechter, Yonn (Cities and the Global Politics of the Environment,, 2019)
The recent rise of cities in global environmental politics has stimulated remarkable debates about sustainable urban development and the geopolitics of a changing world order no longer defined by tightly bordered national regimes. This book explores this major theme by drawing on approaches that document the diverse histories and emergent geographies of "internationalism." It is no longer possible, the book argues, to analyze the global politics of the environment without considering its various urbanization(s), wherein multiple actors are reforming, reassembling and adapting to nascent threats posed by global ecological decay. The ongoing imposition and abrasion of different world orders-Westphalian and post-Westphalian-further suggests we need a wider frame to capture new kinds of urbanized spaces and global green politics. The book will appeal to students, scholars, and practitioners interested in global sustainability, urban development, planning, politics, and international affairs. Case studies and grounded examples of green internationalism in urban action ultimately explore how select city-regions like Cape Town, Los Angeles, and Melbourne are trying to negotiate and actually work through this postulated dilemma.